Nutritional status of children of urban low-income communities, Brazil (1986) - Molina,Maria Carmen Bisi (1989)
During the second half of 1986 the health and nutritional status of 254 children aged up to six years was studied, as well as the socio-economic situation of their parents in two favelas (shantytowns) in Belo Horizonte, Brazil. The nutritional status of the children was characterized by stunting (Z-score: 20.1% < -2) but not by wasting (Z-score: 3.7% < -2). Consideration was also given to how far stunting was caused by high morbidity such as acute respiratory infections (point prevalence: 38.5%), diarrheal diseases (point prevalence: 11.5%) and parasitosis (point prevalence: 70.3%). Furthermore, anemia (point prevalence: 29.7%) appeared as another health problem. The most important determinant of anthropometric indices turned out to be the mother's schooling. From the present data it can be hypothesized that the nutritional status of the children was limited less by the lack of food than by their poor health status.